Rastreamento em células in vitro de uma fosfolipase A2 da peçonha de Bothrops alternatus por meio de pontos quânticos de tamanhos mágicos - Dias, Edigar Henrique Vaz (2019)
Phospholipases A2 represent a family of enzymes with important application in medicine. However, direct tracking in cells has been difficult due to the absence of a stable, effective and specific marker for these enzymes. Magic-sized quantum dots (MSQDs) are nanocrystals of extremely small size and with unique physical properties. In addition, they are excellent biocompatible luminescent markers and can be conjugated to various biomolecules. In this work, we labelled BaltPLA2, a PLA2 isolated from Bothrops alternatus snake venom, with Cadmium selenide (CdSe)/cadmium sulphate (CdS) MSQDs. Bioconjugation was confirmed using infrared spectra and fluorescence microscopy, which demonstrated that the CdSe/CdS MSQDs interact with BaltPLA2 without interfering with its catalytic activity. This probe allowed the tracking of BaltPLA2 since its entry through the plasma membrane to its incorporation into the myoblast nucleus. Complementary studies were carried out to evaluate the antiviral activity of BatPLA2 against the dengue virus. Our tests showed a decrease of approximately 72% 50%, 56% of the cytotoxicity caused by DENV2 infection in the virucidal, post-treatment and adsorption assays, respectively. Thus, the results demonstrated the antiviral activity of BaltPLA2 and that this protein could be an important tool for the development of therapeutic alternatives in the future.